West African Soldiers in Britain's Colonial Army, 1860-1960 - Stapleton, Timothy J. (Timothy Joseph), 1967- (Book collections on Project MUSE., 2021)
"West African Soldiers in Britain's Colonial Army, 1860-1960 explores the history of Britain's West African colonial army based in Nigeria, Ghana, Sierra Leone and the Gambia placing it within a broader social context and emphasizing, as far as possible, the experience of the ordinary soldier. The aim is not to describe the many battles and campaigns fought by this force but to look at the development of the West African colonial army as an institution over the course of about a century. In pursuing this goal, it is sometimes useful to employ the lens of military culture defined differently by scholars but essentially meaning a set of shared ideas and behaviors that inform daily life in the military. While other locally recruited colonial militaries in Africa have attracted considerable attention from historians as they served as an essential pillar supporting European rule, this book represents the first comprehensive scholarly study of Britain's West African army which was the largest such British-led force south of the Sahara. The study is based on extensive archival research conducted in nine archives located in five countries"--